2012
DOI: 10.3892/or.2012.2171
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of SDF-1α on a CD44+ CXCR4+ squamous cell carcinoma cell line as a model for interactions in the cancer stem cell niche

Abstract: Stromal cell-derived factor-1α (SDF-1α), also known as CXCL12, has variable effects on a plurality of cells. It is known to have selective effects on cell migration, morphology, survival and cell homing. As such the SDF-1-CXCR4 axis is postulated to be a crucial key pathway in the interaction between (cancer) stem cells and their surrounding supportive cells, the so-called (cancer) stem cell niche. We evaluated the expression of CD44 as a cancer stem cell (CSC) marker and the expression of CXCR4 in the head an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The mechanism in this work was not defined however they did report that the AHSG-associated migration activity of primary keratinocytes is largely independent of EGFR signaling and did not involve AKT1 or CDC42. However, Faber et al found that SDF-1α had great effect on migration in CD44þCXCR4þHNSCC cell lines [25, 26]. We recently showed that purified fetuin-A was a powerful chemo-attractant for breast and colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism in this work was not defined however they did report that the AHSG-associated migration activity of primary keratinocytes is largely independent of EGFR signaling and did not involve AKT1 or CDC42. However, Faber et al found that SDF-1α had great effect on migration in CD44þCXCR4þHNSCC cell lines [25, 26]. We recently showed that purified fetuin-A was a powerful chemo-attractant for breast and colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…To give a few, selected examples: In gastric-CIC, flow-stimulated invasion was reduced by a blockade of CXCR4, SDF1, and/or CD44 (Kingsmore et al, 2016); in HNSCC, formation of podia and cell migration essentially depend on CD44 and CXCR4 expression (Faber et al, 2013). There is evidence that particularly CD44v6 contributes to CIC migration in response to SDF1.…”
Section: Cd44/cd44v6 Associations Contributing To Cic Motility and Inmentioning
confidence: 99%
“…The significance of the SDF-1-CXCR4 axis is well-discussed in the hematopoietic system. However, to the best of our knowledge, the present study was the first to show that HNSCC cells also demonstrate podia formation as a pre-condition for locomotion using dose-dependent migration towards an SDF-1 gradient (14). In summary, the SDF-1-CXCR4 axis may also play a crucial role in the development, progress, invasion and metastasis of HNSCC and may be an essential pathway in the interaction between CSCs in HNSCC and the surrounding supportive niche.…”
Section: Discussionmentioning
confidence: 68%
“…Clatot et al revealed that the intratumoral level of SDF-1 correlated with survival in HNSCC (32). By contrast, the concentration of SDF-1 in the peripheral blood of HNSCC patients was not observed to differ in comparison with healthy donors (14). The latter findings are consistent with the results of the present study, which suggest that the SDF-1-CXCR4 axis may be involved in the CSC niche within the tumor, but not in the periphery of the blood system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation